The UN Security Council and the international criminal court : the referral mechanism in theory and practice - Lentner, Gabriel M. (Elgar international law, 2018)
Drawing on both theory and practice, this insightful book offers a comprehensive analysis of the relationship between the United Nations Security Council (UNSC) and the International Criminal Court (ICC), centered on the referral mechanism. Arguing that the legal nature of the referral must be conceptualized as a conferral of powers from the UNSC to the ICC, the author explores the complex legal relationship between interacting international organizations. With a novel approach to the relationship between the UNSC and the ICC, this book addresses important questions raised in practice. In particular, Gabriel M. Lentner explores issues regarding any limits and conditions for referral under the UN Charter and the Rome Statute, and the legal effects on heads-of-state immunity, as well as the validity of jurisdictional exemptions for other specific categories of nationals. This is a persuasive study into the powers of the UNSC with respect to international criminal law. With its timely focus on an important topic, this book will be vital reading for academics in international institutional law, international criminal law, and human rights law. ICC judges and lawyers, as well as lawyers involved in the UN, governments, and non-governmental organizations will also benefit from this book.